A novel decision support tool for assessing the suitability of designbuild method for civil construction projects in Malaysia - Lee, Zheng Ping (2022)
Project delivery method is a crucial decision that determines the quality of construction projects. The two main project delivery methods used in construction projects are designbuild (DB) and design-bid-build (DBB), which are comparable in terms of project quality, decision strategies, and risk factors. Although the DB method is prominent among practitioners, experts, and scholars; only a handful of studies have assessed a decision support tool (DST) to determine the suitability of a DB procurement method in civil construction projects. The decision-making process in civil construction projects heavily relies on the suitability of DB methods, which is also dictated by many factors and drivers. The decision support for any civil project depends on client, consultant, and contractor – the main players who ascertain project success. Past studies revealed that poor information sharing, low performance of decision models, and diverse project characteristics as the most common barriers that fail the DSTs in civil construction projects. Multiple projects are being undertaken across many countries and in diverse domains, such as building, highway, and underground civil projects. Referring to the study findings, a Decision Support Tool for Design-Build (DST-DB) was developed in this study to assess the suitability of a DB method in assisting civil construction project experts, contractors, and practitioners to adopt or reject DB for their construction projects, while concurrently preventing project setbacks. The main critical success factors (CSFs) and the DB drivers were identified and compiled from an extensive and in-depth literature review, while crucial inputs were captured from a panel of industry experts. A questionnaire was developed to gather insights from academicians, experts, and workers; while the DST-DB tool was developed to assess the suitability of the DB method by validating the identified factors and drivers. A total of 111 participants were involved in this study and the quasi-experiment method was conducted to compare the performances of practitioners, experts, and academicians specifically from clients, consultants, and contractors working in prestigious firms across Malaysia. The practitioners selected two commonly applied construction project methods; DST-DB and conventional decision-making methods. The decision-making performances retrieved from the two methods were ranked based on a set of conditions using an actual project to exhibit the practical value of the findings. All data were analyzed using multivariate analysis techniques, such as normalized value (NV), standard deviation (SD), and one-way analysis of variance (ANOVA). The results showed that the key performance measures of DST-DB (i.e., usability, likelihood, precision, confidence, and satisfaction) were higher than those recorded for conventional decision-making process in the civil construction projects undertaken in Malaysia. The pre- and post-surveys revealed that the DST-DB effectively improved the decision-making performance based on the key selection factors used in most countries (i.e., effective client briefing, maximizing resources, and sharing of expertise). Essentially, this study is one of the first decision support studies executed for DB construction projects that captured direct assessment and view from three main stakeholders of civil construction project practitioners (project clients, consultants, and contractors). The study outcomes may serve as a reference for assessing the project delivery method for civil construction projects, a resource for academic scholars working in construction projects domain, and a guide for construction practitioners to enhance their decision-making process. This study paints a comprehensive picture for a DB construction project to embark upon and accomplish future decision-making process.